Analisis Faktor-Faktor Yang Mempengaruhi Kepuasan Pelanggan Produk Telkom Indihome Di Wilayah Kota Surakarta Tahun 2015 - PUSPITA, Try Baskara; , Drs. Joko Suwandi, SE., M.Pd (2015)
The purpose of this research is: 1) For knowing the influence of the quality of the product in level of customer's satisfaction of Telkom products in the region of Surakarta Indihome 2015. 2) For knowing the influence of the quality of service in level of customer's satisfaction of Telkom product Indihome in the region of Surakarta 2015. 3) For knowing the influence of price in level customer's satisfaction Telkom product Indihome in the region of Surakarta 2015. 4)For knowing the influence of product quality, service quality and price in level of customer's satisfaction of Telkom products Indihome in the region of Surakarta 2015. Research on associative quantitativetook in PT Telkom Indi home in the region of Surakarta 2015. It takes samples 100 customers from a population of 11.287 customers, techniques of data collection by using question form. Technique of Data analysis that are used to test the hypothesis is regression analysis linear are three predictors, t-test and F-test besides that is done bythe calculation of the coefficient of determination, the relative contribution and effective contribution. The conclusions of this research are: 1) there is a positive influence on the quality of products in level customer's satisfaction of Telkom product Indihome in the region of Surakarta 2015. 2) There is a positive influence on the quality of service towards the customer's satisfaction of Telkom product Indihome in the region of Surakarta 2015. 3) There is a positive influenceon the price of customer's satisfaction Telkom product Indihome inthe region of Surakarta 2015. 4) There is a positive influence product quality, service quality and customer's satisfaction in price of the Telkom product Indihome in the region ofSurakarta 2015. From the result of the analysis of the data is gotten the value of the coefficient of determination R2 of 0,326 which indicates that a variable combination of product quality, service quality and price of 32,60%, while the rest are influenced by 67,40% other variables not examined. Keyword: customer satisfaction, product quality, price and service quality